Spondyloarthritis and the Human Leukocyte Antigen (HLA)-B*27 Connection - Kavadichanda, Chengappa G.; Geng, Jie; Bulusu, Sree Nethra; Negi, Vir Singh; Raghavan, Malini (Frontiers in Immunology, 2021)
Heritability of Spondyloarthritis (SpA) is highlighted by several familial studies and a high association with the presence of human leukocyte antigen (HLA)-B*27. Though it has been over four decades since the association of HLA-B*27 with SpA was first determined, the pathophysiological roles played by specific HLA-B*27 allotypes are not fully understood. Popular hypotheses include the presentation of arthritogenic peptides, triggering of endoplasmic reticulum (ER) stress by misfolded HLA-B*27, and the interaction between free heavy chains or heavy chain homodimers of HLA-B*27 and immune receptors to drive IL-17 responses. Several non-HLA susceptibility loci have also been identified for SpA, including endoplasmic reticulum aminopeptidases (ERAP) and those related to the IL-23/IL-17 axes. In this review, we summarize clinical aspects of SpA including known characteristics of gut inflammation, enthesitis and new bone formation and the existing models for understanding the association of HLA-B*27 with disease pathogenesis. We also examine newer insights into the biology of HLA class I (HLA-I) proteins and their implications for expanding our understanding of HLA-B*27 contributions to SpA pathogenesis.